Evaluation of Knowledge, Attitude and Practice regarding Positron Emission Tomography Scan among UG, Interns & PG students: A Survey Study - George, Balu; Chavan, Mahesh; Hamid, Nida; Bhanawat, Nilesh; Tiwari, Rahul VC; Gulia , Sunil Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Background: Positron Emission Tomography (PET) provides a highly sensitive and specific way of diagnosing and monitoring tumour cells. Knowledge and awareness regarding PET is crucial to oncologic imaging. Objective: To evaluate the knowledge, attitude and practice regarding Positron Emission Tomography Scan among undergraduate, Intern & postgraduate medical students. Material and Methods: A questionnaire comprising of questions on knowledge, attitude and practice regarding PET scan was sent to 300 UG, intern and PG medical students via email and social media platforms. The 179 responses received were documented and comparisons were made between the groups. Results: 55.56% of UG medical students did not have knowledge of F-fluorodeoxyglucose as the most commonly used radioactive tracer in PET scans. 68.52% of the UG medical students were unaware what a ‘hotspot’ represented in a PET scan, 64.56% and 89.13% of interns and PG medical students chose the correct answer. 72.22%, 86.08% and 97.83% of UG, intern and PG students respectively, agreed that PET scan helps in determining biochemical and physiological activity of tumours. Conclusion: PG students displayed the greatest knowledge concerning PET scan. Medical students accept the importance and utility of a PET scan in oncologic imaging.